Morphological Effect on Swelling Behaviour of Carboxymethyl Cellulose–Maleic Acid Hydrogel Modified with Kombucha Bacterial Cellulose - Siahaan, Tanty N.; Basuki, Basuki; Siregar, Amir H.; Muthawali, Dede I. (Jurnal Akademika Kimia, 2023)
The incorporation of bacterial cellulose from kombucha tea in carboxymethyl cellulose / maleic acid (CMC / MA) hydrogels has been successfully conducted. This study aims to analyze the relationship between the pores on the surface of the hydrogel with their water-absorbing ability. Bacterial cellulose from kombucha (KBC) was confirmed by the spectrum of OH, C-O-C, and C-OH functional groups with FT - IR analysis. Filler KBC was added to CMC / MA hydrogel with variations in the concentration of 2, 4, 6, and 8 % wt. The CMC / MA / KBC hydrogels were characterized by swelling test, degree of crosslinking, FTIR, and SEM. The swelling results showed that hydrogels with 2 % KBC produced the best water absorbing ability up to 172 %, water absorption decreased with the increase of KBC concentrations. Furthermore, SEM image results showed that the addition of KBC affects the morphological shape and pore size of the hydrogel. Meanwhile, FTIR analysis showed that there were no major changes in the functional groups of hydrogels.